Phenomenology of Delusions and Hallucinations in Patients with Schizophrenia - Gecici, Omer; Kuloglu, Murat; Guler, Ozkan; Ozbulut, Omer; Kurt, Erhan; Onen, Sinay; Albayrak, Yakup (Kure Iletisim Grubu A S, 2010)
Background: The aim of this study is to investigate the influence of living in different geographic regions of the same country on the phenomenology of schizophrenic delusions and hallucinations in two groups of schizophrenic patients. Methods: A total of 373 schizophrenic patients hospitalized in three different psychiatric hospitals in Turkey were recruited, and their delusions were classified by using the classification system developed by Huber and Gross. Patients were categorized with respect to regions in which they lived. Group 1 represented the Western region of Turkey, and group 2 represented the Central region of Turkey. Results: Delusions of persecution and reference were detected frequently in both genders and groups. Delusions of poisoning and erotomania were more prevalent in females than in males. The most frequent auditory hallucinations included hearing voices conversing and voices commenting. Seeing goblins was the most prevalent theme in visual hallucinations. Conclusions: The results demonstrate a relationship between the content of delusions and hallucinations and living in different geographic regions of the same country. Although cultural and environmental factors are important in the phenomenology of delusions and hallucinations, the geographic region of residence seems to be great importance in phenomenology as well.
Keywords: Schizophrenia; delusion; hallucination; phenomenology